SNP genome scanning localizes oto-dental syndrome to chromosome 11q13 and microdeletions at this locus implicate FGF3 in dental and inner-ear disease and FADD in ocular coloboma - Gregory-Evans, Cheryl Y.; Moosajee, Mariya; Hodges, Matthew D.; Mackay, Donna S.; Game, Laurence; Vargesson, Neil; Bloch-Zupan, Agnès; Rüschendorf, Franz; Santos-Pinto, Lourdes; Wackens, Georges; Gregory-Evans, Kevin (My University, 2007)
We ascertained three different families affected with oto-dental syndrome, a rare but severe autosomal-dominant craniofacial anomaly. All affected patients had the unique phenotype of grossly enlarged molar teeth (globodontia) segregating with a high-frequency sensorineural hearing loss. In addition, ocular coloboma segregated with disease in one family (oculo-oto-dental syndrome). A genome-wide scan was performed using the Affymetrix GeneChip10K 2.0 Array. Parametric linkage analysis gave a single LOD score peak of 3.9 identifying linkage to chromosome 11q13. Haplotype analysis revealed three obligatory recombination events defining a 4.8 Mb linked interval between D11S1889 and SNP rs2077955. Higher resolution mapping and Southern blot analysis in each family identified overlapping hemizygous microdeletions. SNP expression analysis and real-time quantitative RT-PCR in patient lymphoblast cell lines excluded a positional effect on the flanking genes ORAOV1, PPFIA1 and CTTN. The smallest 43 kb deletion resulted in the loss of only one gene, FGF3, which was also deleted in all other otodental families. These data suggest that FGF3 haploinsufficiency is likely to be the cause of otodental syndrome. In addition, the Fas-associated death domain (FADD) gene was also deleted in the one family segregating ocular coloboma. Spatiotemporal in situ hybridization in zebrafish embryos established for the first time that fadd is expressed during eye development. We therefore propose that FADD haploinsufficiency is likely to be responsible for ocular coloboma in this family. This study therefore implicates FGF3 and FADD in human craniofacial disease. © The Author 2007. Published by Oxford University Press. All rights reserved.